2015
DOI: 10.1063/1.4922023
|View full text |Cite
|
Sign up to set email alerts
|

Spot profile analysis and lifetime mapping in ultrafast electron diffraction: Lattice excitation of self-organized Ge nanostructures on Si(001)

Abstract: Ultrafast high energy electron diffraction in reflection geometry is employed to study the structural dynamics of self-organized Germanium hut-, dome-, and relaxed clusters on Si(001) upon femtosecond laser excitation. Utilizing the difference in size and strain state the response of hut- and dome clusters can be distinguished by a transient spot profile analysis. Surface diffraction from {105}-type facets provide exclusive information on hut clusters. A pixel-by-pixel analysis of the dynamics of the entire di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The pattern was recorded at a sample temperature of 25 K, with an electron energy of 20 keV and a grazing angle of incidence of 3.2. We will show that several specific diffraction features allow a clear identification and separation of spot intensities from hut and dome clusters [28]. In particular, this includes hut cluster spots and spots composed of contributions from both hut and dome clusters.…”
Section: Resultsmentioning
confidence: 88%
“…The pattern was recorded at a sample temperature of 25 K, with an electron energy of 20 keV and a grazing angle of incidence of 3.2. We will show that several specific diffraction features allow a clear identification and separation of spot intensities from hut and dome clusters [28]. In particular, this includes hut cluster spots and spots composed of contributions from both hut and dome clusters.…”
Section: Resultsmentioning
confidence: 88%
“…Finally, heterogeneous chemistry, relevant to applications in catalysis, is an extremely important area for exploration. There has been great progress in developing femtosecond reflected high-energy electron diffraction (RHEED) for surface studies and LEED approaches using nanotips for the shortest propagation distances possible to maintain time resolution. These studies have revealed very interesting cooperative surface effects. In terms of surface chemistry, the main challenge is the irreversible nature of surface reaction dynamics.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…Turning disadvantage into opportunities, ultrafast electrons have been used to monitor the transient electric field distribution of various materials beyond TR-RHEED application. [8,83] Attaching molecules, nanoparticles, [84] or low dimension structures on a surface [85] create new opportunities to study catalysis, functional materials, and sample-substrate correlations by UED, yet this field is still waiting for further exploration.…”
Section: Surface Science and Beyondmentioning
confidence: 99%